Keterlambatan Pemerolehan Bahasa (Speech Delay) pada Anak Usia 6 Tahun serta Implikasinya dalam Pendidikan Anak Usia Dini: Studi Kasus terhadap Kenzo - Sri Ramayeni; Yetty Morelent; Syofiani Syofiani (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2026)
This study aims to describe the characteristics, contributing factors, and impacts of a language acquisition delay (speech delay) experienced by Kenzo, a six-year-old boy in Nagari Sunur, Padang Pariaman Regency, and to formulate its implications for early childhood education. This research employs a qualitative approach using a single case study method. Data were collected through participatory observation, in-depth interviews with the subject's mother and teacher, and documentation of speech recordings, then analyzed using the Miles and Huberman interactive model. The findings show that Kenzo's language delay appears across all linguistic levels: sound substitution and elision at the phonological level, absence of quantity markers at the morphological level, single-word-dominated utterances with a mean length of utterance (MLU) of 1.33 words at the syntactic level, accurate lexical meaning not yet developed into compositional meaning at the semantic level, and reliance on gestures with delayed responses at the pragmatic level. Contributing factors include the child's low self-confidence (internal) as well as limited verbal interaction at home, passive gadget use, and restricted peer interaction (external). These conditions affect Kenzo's communication ability, social interaction, self-confidence, and participation in learning. The study recommends strengthening early detection, verbally rich teaching strategies, and school–parent partnerships as a comprehensive response within early childhood education settings.